Demonstrasi Pembuatan Pupuk Orgaik Cair (POC) guna Menekan Penggunaan Pupuk Sintetis di Desa Tanjunganom, Salaman - Rini Setiawati; Shandya Alonso Eka Renanda; Seftiyani Kusumaningrum; Rizky Mutiara Dewi; Renita Erlien Sapalinda; Indria Nur Khasanah; Adi Wahyu Anugra; Rizky Mahendra; Muhammad Syaiful Fadhli; Rahmi Ma’rufah Ashodhiqoh; Septian Tri Nugroho (BADAN PENERBIT STIEPARI PRESS, 2025)
The production of liquid organic fertilizer (POC) is a strategic effort to utilize locally available organic waste to improve soil fertility and support the sustainability of agricultural systems. Utilizing organic waste, particularly livestock waste, has significant potential to reduce farmers' dependence on chemical fertilizers, which are known to negatively impact soil ecosystems and the environment as a whole. This community service activity aims to provide residents with knowledge and practical skills regarding the process of producing liquid organic fertilizer using livestock manure as the primary raw material. The POC production process is combined with the use of effective microorganisms (EM4) in the fermentation stage, resulting in a fertilizer with a more balanced nutrient content and easy plant absorption. The activity implementation method includes counseling to provide a theoretical basis, technical training on the production stages, and live demonstrations in the field to provide residents with practical experience. The results of the activity indicate a significant increase in residents' knowledge and skills regarding liquid organic fertilizer production techniques. Furthermore, there has been a shift in public awareness about the importance of utilizing organic waste as a high-value resource. Compared with chemical fertilizers, which only provide quick results but tend to damage soil structure in the long term, POC is more environmentally friendly, improves soil quality, and is more economical because it can be produced independently using local resources. Thus, this community service activity not only increases the capacity of residents in managing waste, but also encourages the creation of environmentally friendly sustainable agricultural practices, reduces dependence on chemical fertilizers, and contributes to improving the welfare of farmers.